Research and Development Work Carried out by the Chair of Engineering Geodesy and Measurement and Control Systems, Faculty of Geodesy and Cartography WUT – Thematic Scope and Achievements - Nowak Edward; Malarski Ryszard; Prószyński Witold; Sadowska Alicja; Woźniak Marek; Zaczek-Peplinska Janina (Reports on Geodesy and Geoinformatics, 2016)
Geodetic engineering surveys are an important part of the works carried out by the Faculty of Geodesy and Cartography, Warsaw University of Technology. These works concern measurement techniques as well as advanced result analysis methods applied in precise industrial surveys and in processes controlling object’s behaviour over time.